Climate-smart agricultural practices in rural Ethiopia: The gender-differentiated impact of land rights knowledge - Quisumbing, Agnes R.; Kumar, Neha (International Food Policy Research Institute, 2014)
This policy note summarizes research examining the medium-term impact of land registration in Ethiopia on household investment behavior, specifically in terms of the adoption of soil conservation techniques and tree planting. The research investigated whether men’s and women’s knowledge of their land rights—defined as tenure security, land transfer rights, and rights related to gender equity and inheritance—had an impact on their investment behavior.